2018
DOI: 10.1097/rli.0000000000000414
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proton Spectroscopy of the Testes at 3 T

Abstract: Testicular metabolite concentrations, measured by proton spectroscopy at 3 T, may be valuable as noninvasive biomarkers of spermatogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…The results of our study demonstrated low normalized concentrations of Cho in NOA men. Similar results were reported by previous studies 15–17 . Based on literature data, 11,12,14–17 Cho appears to be a useful noninvasive fingerprint of spermatogenesis.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results of our study demonstrated low normalized concentrations of Cho in NOA men. Similar results were reported by previous studies 15–17 . Based on literature data, 11,12,14–17 Cho appears to be a useful noninvasive fingerprint of spermatogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…Data on the usefulness of proton MRS in assessing the biochemical composition of human testes are still preliminary 5,11–19 . Pathologic alterations in metabolic peaks have been reported in testes with impaired spermatogenesis and testicular mass lesions 5,14–19 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study suggested that testicular metabolite concentrations measured by 3T proton spectroscopy can be used as non-invasive biomarkers to predict spermatogenesis. 71 A study showed that phosphocholine concentrations were significantly higher in normal testes compared with Sertoli cells only. 72 This finding indicated that the unique metabolic profile of spermatogenesis may be identified by proton magnetic resonance spectroscopy, which is helpful in non-invasive diagnosis of spermatozoa in men with NOA.…”
Section: Factors Predicting the Srr In Patients With Noa Before Surgerymentioning
confidence: 99%